2007
DOI: 10.1111/j.1600-0854.2007.00645.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophins Redirect p75NTR from a Clathrin‐Independent to a Clathrin‐Dependent Endocytic Pathway Coupled to Axonal Transport

Abstract: The p75 neurotrophin receptor (p75 NTR ) plays multiple roles in neuronal physiology through interactions with many ligands and coreceptors. However, its intracellular neuronal trafficking prior to and after neurotrophin activation is still poorly characterized. We have previously shown that in response to nerve growth factor (NGF), p75 NTR is retrogradely transported along the axons of motor neurons (MNs) in carriers shared with NGF, brainderived neurotrophic factor and the tyrosine kinase receptor TrkB. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
83
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 45 publications
9
83
0
Order By: Relevance
“…Plasmids encoding wild-type and mutant p75 NTR were microinjected into embryonic spinal motoneurons, and axonal trafficking of the expressed receptors was visualized by time-lapse confocal microscopy using antibodies against their N-terminal hemagglutinin (HA) epitope tag. As previously reported (Deinhardt et al, 2007), very few retrograde carriers containing wild-type p75 NTR were detected in the absence of NGF, but these were greatly increased upon NGF addition (Fig. 7A,B).…”
Section: Disulfide-crosslinked P75supporting
confidence: 63%
See 2 more Smart Citations
“…Plasmids encoding wild-type and mutant p75 NTR were microinjected into embryonic spinal motoneurons, and axonal trafficking of the expressed receptors was visualized by time-lapse confocal microscopy using antibodies against their N-terminal hemagglutinin (HA) epitope tag. As previously reported (Deinhardt et al, 2007), very few retrograde carriers containing wild-type p75 NTR were detected in the absence of NGF, but these were greatly increased upon NGF addition (Fig. 7A,B).…”
Section: Disulfide-crosslinked P75supporting
confidence: 63%
“…First, we looked at axonal retrograde transport of p75 NTR complexes, which is a prerequisite for cell body-mediated responses to p75 NTR signaling in neurons. Although the specific signaling steps leading to retrograde transport of p75 NTR are still unknown, this process has recently been shown to be ligand mediated (Deinhardt et al, 2007). Plasmids encoding wild-type and mutant p75 NTR were microinjected into embryonic spinal motoneurons, and axonal trafficking of the expressed receptors was visualized by time-lapse confocal microscopy using antibodies against their N-terminal hemagglutinin (HA) epitope tag.…”
Section: Disulfide-crosslinked P75mentioning
confidence: 99%
See 1 more Smart Citation
“…For other endocytosing receptors, we know that signaling outcomes can differ in important ways depending on the endocytic route taken (clathrin-dependent or -independent) and the subsequent postendocytic trafficking (recycling endosome, late endosome, etc.) (for examples see Deinhardt et al 2007;Le Roy and Wrana 2005). Furthermore, the residence time in these signaling endosomes can also be regulated and greatly influence signaling outcomes (Zoncu et al 2009).…”
Section: Regulation Of Local Endocytosismentioning
confidence: 99%
“…7, D and E). Previous studies have shown that the internalization of TrkA is dependent on dynamin (51,52). We, therefore, used a dominant-negative form of dynamin (dynamin-K44A, DN-dynamin) to test whether we could suppress GFP-TrkA internalization.…”
Section: Identification Of Mint2 As a Potential Binding Partner Of Trmentioning
confidence: 99%